MULTI-CRITERIA DECISION MAKING FOR SMES SUSTAINABILITY ASSESSMENT - Febrina Agusti; Fery Fery Wisnu Saputro; Indah Wahyu Utami; Fertilio Dwyanto (Proceeding of International Conference on Science, Health, And Technology, 2022)
The importance of SMEs to world economic and are pillars of the country's economic development. The number of SMEs was increased from year to year in the world. The number of SMEs in ASEAN alone currently reaches more than 70 million business units and cover 99% of all businesses in the region. Directly proportional to it, competition and sustainability vulnerabilities also getting higher. Sustainability issues had been the main focus for SMEs. Sustainability was based on three main baselines (economic, social, and cultural). Currently, a tool needed to assessment sustainability and develop a competitive strategy for these SMEs. However, the tools for sustainability assessment in SMEs was not available. This study aims to develop a sustainability assessment tool in the SMEs sector. Multi-Criteria Decision Making (MCDM) was a framework that supports the decision-making process by combining several baselines. One of the MCDM methods that can be used was the Analytical Hierarchy Process (AHP).